2019
DOI: 10.3389/fphar.2019.01007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Tolerability of Repeated Courses of Viscosupplementation in Symptomatic Hip Osteoarthritis: A Retrospective Observational Cohort Study of High Molecular Weight vs. Medium Molecular Weight Hyaluronic Acid vs. No Viscosupplementation

Abstract: Background: Nonsurgical management of symptomatic hip osteoarthritis needs real-world evidence. We evaluated the effectiveness and tolerability of US-guided intra-articular treatment of two hyaluronic acids (HAs) commercially available in Italy and investigated predictors of response. Methods: Outpatient records including three cohorts: 122 subjects treated with medium (1,500–3,200 kDa; Hyalubrix®) molecular weight (MW) or high (hylan G-F20; Synvisc®) MW HAs and 20 controls taking NSAIDs/analgesics on demand w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 30 publications
2
19
0
6
Order By: Relevance
“…Generally, one to four injections are recommended with the ultrasound-guided infiltration technique, which is the safest approach [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, one to four injections are recommended with the ultrasound-guided infiltration technique, which is the safest approach [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of HA injection into the knee showed that the improvement of pain and function compared to the placebo group depended on the type of HA, and that Hylan G-F 20 did result in such improvements. 41) Whereas most hip injection studies do not have a placebo group, [10][11][12][13][14][15] there are three studies of hip injection that compare the HA group with a placebo group and show no difference between them. 42) However, Brander et al evaluated the effects of HA-IA using the Western Ontario McMaster Universities Osteoarthritis Index, in which the pain score is classified into five levels and subtle differences at the same level could be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…8) For hip OA, several studies have reported that pain is reduced in the short-term by IA-HA, and function disability is improved. [10][11][12][13][14][15][16] These reports are from Europe and the United States, because the use of HA for hip OA is not covered by insurance in Japan and is therefore rarely used. Hylan G-F 20 is a cross-linked sodium hyaluronate with a high average molecular weight of 6 million Dalton.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis found that intra-articular placebo is effective for osteoarthritis, particularly with regards to self-reported pain and functional outcome measurements, probably due to the dilution of proinflammatory cytokines by saline [72]. Regarding the different concoctions, published data showed that most hyaluronic acid formulations were not significantly different in terms of clinical and functional outcomes [73][74][75].…”
mentioning
confidence: 99%
“…Indeed, studies using intra-articular corticosteroids in the hip suggest a short duration of action (4-12 weeks) [67,76,77]. In contrast, the effects of hyaluronic acid can last up to 6 months, although recent evidence also showed no difference at this time point for hyaluronic acid and corticosteroids [60,74,75,78]. A systematic review included five trials investigating the use of PRP in hip osteoarthritis, showing overall no significant differences between patients treated with PRP or hyaluronic acid alone [79].…”
mentioning
confidence: 99%